Effects of Twist1 on drug resistance of chronic myeloid leukemia cells through the PI3K/AKT signaling pathway - Yuan, Ruilan; Chang, Jin; He, Jianxia (Cellular and Molecular Biology, 2020)
This study aimed to investigate the effects of Twist1 on the drug resistance of chronic myeloid leukemia (CML) cells through the PI3K/AKT signaling pathway. K562 and KCL-22 cells were modeled for imatinib resistance, so as to analyze the effects of inhibiting Twist1 and the pathway on the therapeutic effect of imatinib on imatinib-resistant CML cells, and to find the mechanism of action of Twist1 on affecting the resistance. After the CML cells were successfully resistant to imatinib, Twist1 expression increased again in the cells and the PI3K/AKT signaling pathway was further activated. After the silence of the Twist1 expression, the imatinib-resistant CML cells were more sensitive to imatinib, and the PI3K/AKT signaling pathway was inhibited, and the expression level of p-AKT protein significantly reduced. According to further experiments, imatinib enhanced its inhibitory effect on the growth of the imatinib-resistant CML cells after the activation of the pathway was inhibited by an LY3023414 inhibitor. In conclusion, Twist1 and the PI3K/AKT signaling pathway are over-activated during the formation of the CML cells resistant to imatinib. The silence of Twist1 can reverse the resistance through the pathway.